Assessment of the Antioxidant Potential of Blackthorns and Hawthorns: Comparative Analysis and Potential Use in Ruminants’ Nutrition - Alexandra-Gabriela Oancea; Mihaela Saracila; Petru Alexandru Vlaicu; Iulia Varzaru; Arabela Elena Untea; Catalin Dragomir (Separations)
The food industry is intensifying its effort to enrich food composition in various nutrients through animal feeding, but these challenges can be limited by the costly feed resources, water scarcity, and pesticide pollution, making it crucial to explore alternative feedstuffs with fewer requirements. Blackthorns and hawthorns are characterized by their rich phytochemical and antioxidant profiles, suggesting their potential to enhance the performance of ruminants though the supply of bioactive substances. Our study revealed their rich composition of micronutrients; hawthorns showed a remarkable amount of polyunsaturated fatty acids (57.23 g FAME/100 g total FAME), particularly omega-3 and omega-6, while blackthorn presented higher concentration of monounsaturated fatty acids, specifically oleic acid (56.99 g FAME/100 g total FAME). In terms of lipo-soluble antioxidants, blackthorn exhibited higher levels of xanthophyll and vitamin E (123.83 mg/kg DM), including its isomers (alpha, gamma, and delta). Concerning the water-soluble antioxidants, hawthorns showed elevated composition of the total content of flavonoids and polyphenols, comparing with blackthorn. Moreover, hawthorns showed a high antioxidant capacity, as assessed through DPPH, ABTS, and TAC analyses. In terms of the scavenging capacity of blackthorn and hawthorn against superoxide radicals, blackthorn had higher radical scavenging potential against superoxide radicals, compared to hawthorn.